The Effect Of Combination Of Retrowalking Exercise And Static Contraction In Increasing Activity Daily Living Functions In Knee Osteoarthritis Risk Tea Pickers - Wildha Rosita Dewanti; Nurul Aini Rahmawati (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
The tea picker job involves a lot of standing, wich puts pressure on the knees. This routine activity can cause musculoskeletal problems, such as osteoarthritis, which can reduce tea pickers’ daily living activity in tea pickers at risk of osteoarthritis which can be handled by retrowalking exercise and static contraction in increasing the function of daily living activity in tea pickers at risk of knee osteoarthritis. Research Methods: This study used a quasi – experimental design (one group desihn pre – test and post – test) involving 31 sampels of tea pickers. This research was cinducted for 4 weeks with 3 times a combination of retrowalking exercise and static contraction in a week. This study uses The Western Ontario and McMaster University Osteoarthritis Index (WOMAC) as an instrument to regulate daily living activity risk of knee osteoarthritis in tea pickers. Results : The test using the Paired Sample t Test showed a value of 0.000 (p < 0.05) which means that it has a normal contribution. Conclusion : There is an effect of a combination of retrowalking exercise and static contraction in increasing daily living activity risk of knee osteoarthritis in tea pickers. Suggestion : For future researchers, the result of study can be used as a reference for students, educator and physiotherapy regarding the effect of the combination of retrowalking exercise and static contraction on increasing the function of daily living activities in the risk takers of knee osteoarthritis.